Effect of working place infection control practices on workers' psychological distress: A large-scale cohort study during the COVID-19 pandemic in Japan - Kodama, Toyohiko; Ishimaru, Tomohiro; Tateishi, Seiichiro; Hino, Ayako; Tsuji, Mayumi; Ogami, Akira; Nagata, Tomohisa; Matsuda, Shinya; Fujino, Yoshihisa (Frontiers in Psychiatry, 2022)
Background The COVID-19 pandemic has dramatically transformed the work environment and practices worldwide. Long-term infection control practices may increase the psychological distress of workers, and, conversely, inadequate infection control practices in the working place may increase the fear of infection. This study aimed to determine the relationship between infection control practices in the working place and employee mental state during the COVID-19 pandemic in Japan. Methods This study was conducted in December 2020 and February 2021. The participants had undergone a preliminary survey, which revealed that they were in a good mental state. Their psychological distress was investigated via a second survey, and the factors associated with distress were studied using a logistic model. Results The results of the second survey indicated that 15.3% of participants demonstrated psychological distress. This was associated with leave-of-absence instructions, instructions for shortening business hours, and requests to avoid the working place in case of any symptoms. Conclusion The study found that while some infection control practices reduce workers' distress, others worsen it. Employers need to consider infection control practices as well as the worsening mental state of employees following a decrease in income caused by such measures. Follow-up studies may be necessary to clarify the long-term effects on workers' mental states.